ANGI-01. FIBROBLAST GROWTH FACTOR 13 REGULATES GLIOMA CELL INVASION - Otani, Yoshihiro (Neuro Oncol, 2017)
BACKGROUND: Glioblastoma has a poor prognosis, and its aggressive nature including excessive invasion and angiogenesis. To reveal the invasive mechanisms, we previously established two glioma cell lines (J3T-1 and J3T-2) with different invasive phenotypes. J3T-1 exhibited abundant angiogenesis and tumor cell invasion around neovasculature, while J3T-2 exhibited diffuse cell invasion into surrounding normal parenchyma. METHODS: Invasion-related genes in J3T-2 cells were identified using microarray analyses of both cell lines, and their intracellular and intratumoral distribution patterns were evaluated in J3T-2 cell lines, human glioma cell lines, human glioblastoma stem cells, and human glioblastoma specimens. In addition, we revealed the role of the invasion-related genes in vitro and in vivo. RESULTS: Fibroblast growth factor 13 (FGF13) was up-regulated in J3T-2 cells compared to J3T-1 cells. The expression level of FGF13 was also overexpressed in human glioma cell lines, human glioblastoma stem cells, and human glioblastoma specimens, when compared to that of normal human astrocytes. The RNA-seq data from the IVY Glioblastoma Atlas Project and immunohistochemical staining of glioblastoma specimens showed FGF13 expression in glioma cells in the invasive edges. The intracellular distribution was mainly in the cytoplasm of tumor cells and colocalized with tubulin. Overexpression of FGF13 stabilized tubulin dynamics in vitro and knockdown of FGF13 inhibited glioma invasion both in vitro and in vivo. Moreover, silencing of FGF13 also decreased bevacizumab-induced glioma invasion in vitro and in vivo. CONCLUSIONS: FGF13 regulated glioma cell invasion. Our results suggested that FGF13 could be a promising new target to treat and prevent glioma invasion.